Coexisting Choroidal and Brain Metastases in a Patient with Breast Cancer Treated with Stereotactic Radiotherapy - Giovanni William Oliverio; Giovanni Roberto Tedesco; Claudia Azzaro; Alessandro Meduri; Pasquale Aragona (Case Reports in Ophthalmology, 2022)
Choroidal metastases from breast cancer are the most common ocular malignancies in adults. We report a case of a 37-year-old female with a history of breast cancer who had a sudden blurred vision in her right eye. An ophthalmologic assessment revealed a dome-shaped lesion and a secondary retinal detachment with subretinal fluid in the left eye, suggestive of choroidal metastasis. Moreover, an MRI scan showed the presence of a single brain lesion. The patient was treated with stereotactic radiotherapy, with 300 cGy for 10 days. Six months after treatment, there was a regression of the mass and improvement of visual acuity. Stereotactic radiotherapy is a safe and effective treatment for choroidal metastases and should be considered to treat coexistent choroidal and brain metastatic lesions, to improve survival, visual function, and quality of life.